Aktivitas Antioksidan Ekstrak Etanol Bunga Clitoria ternatea L. Dengan Senyawa Antioksidan (Antosianin dan Mirisetin) - Monica Dewi Ranggaini; Johni Halim; Intan Paramitha Kumaladevi (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: The COVID-19 pandemic is impacting a large number of populations. Patients with cancer infected with this virus require a longer treatment. Cancer occurs due to oxidative stress which creates an imbalance between the production of reactive oxygen species (ROS) and the amount of antioxidants in the body. Antioxidants are needed to balance ROS and increase the body's resistance to infection and disease. Clitoria ternatea L. is known to be one of the natural ingredients that has the potential as a natural antioxidant. It contains active compounds, such as anthocyanin and myricetin which act as antioxidants. Purpose: To find out the comparison of antioxidant activity C. ternatea L. extract in ethanol 70% solvent with the antioxidant compounds of anthocyanin and myricetin. Method: Research with laboratory experimental methods. C. ternatea L. simplicia was extracted using maceration method in 70% ethanol solvent. Antioxidant activity test using the 2,2-diphenyl-l-picrylhydrazyl (DPPH) method was carried out on samples of C. ternatea L. ethanol extract, anthocyanin and myricetin antioxidant compounds with a wavelength of 517 nm to measure their absorbance using a microplate reader. Result: The IC50 value of the ethanol extract of C. ternatea L. was 52.40 mg/mL, the antioxidant compound anthocyanin was 27.68 mg/mL and the antioxidant compound myricetin was 4.89 mg/mL. Conclusion: The antioxidant compound myricetin has very strong antioxidant activity compared to the ethanol extract of C. ternatea L. and the antioxidant compounds of anthocyanins.